Analysis of Narcotics Smuggling from Malaysia Through the Indonesian Sea Route Based on the Perspective of International Law - Ananda, Hauwra; Putri, Margaretha; Putri, Riska Amelia (CV. Rayyan Dwi Bharata, 2023)
Narcotics Smuggling is one of the illegal narcotics distribution activities which may involve the import, export, distribution or illegal production of narcotics and illegal drugs. Narcotics smuggling involves the movement of narcotics across national borders or through illegal channels with the aim of avoiding security and legal controls in force in a country. Narcotics smuggling that still occurs a lot in Indonesia is narcotics smuggling from Malaysia through the Indonesian sea route. In the perspective of International Law, there are national laws and regulations governing narcotics smuggling, which can involve international cooperation in law enforcement and the extradition of perpetrators. International organizations such as the Narcotics and Organized Crime Agency (UNODC) also play a role in providing technical assistance and supporting countries' efforts to prevent and enforce laws against narcotics smuggling.